Major and minor salivary gland tumours. (August 2020) - Gatta, Gemma; Guzzo, Marco; Locati, Laura D.; McGurk, Mark; Prott, Franz Josef
Abstract: Salivary glands carcinomas are very rare epithelial malignant tumors. In 2013 in Europe, 7800 new diagnoses were estimated, 8.5 % of all head and neck cancer. The last WHO classification (2017) counts more than 20 malignant histotypes, this variety as well as the rarity of some of them needs a skilled pathologist for diagnosis. Surgery remains the mainstay of management followed by radiation in high-grade and high-risk pathological features cases. The intensity modulated radiotherapy (IMRT) should be preferred over conformational radiotherapy techniques as adjuvant and exclusive treatment in advanced cases. Particle radiotherapy ( i.e. protons, carbon ions) can have a role in advanced/unresectable disease since it was proved to have better results over photons in loco-regional control both in adenoid cystic carcinoma and in other histotypes. Although chemotherapy is still the most frequent treatment for metastatic patients, several new compounds ( i.e. anti-angiogenic agents, tailored agents, checkpoint inhibitors) are under investigation.